(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
In this article, research was conducted on the growth and development of varieties introduced from the Netherlands in the climatic conditions of the Namangan region of the Republic of Uzbekistan. The material of the experiment, that is, onions, was 2,300,000 pieces of varieties introduced from the Netherlands. Before planting, tulip bulbs were subjected to refrigeration technology at a temperature of 4-50C for 16 weeks. The main goal of the research was to identify onion varieties that are fruitful, resistant to all climatic conditions and diseases, and to compare local and introduced varieties, to determine the most optimal options.